Physical characteristics of quail (Coturnix coturnix) meat given hydrolyzed feather meal from broiler at different levels. (March 2019) - Said, M I; Abustam, E; Pakiding, W; Mide, M Z; Basri, S
Abstract: The quail ( Coturnix-coturnix ) is a type of bird that has recently been widely cultivated. One factor that can affect the physical quality of quail meat is feeding. The need for food ingredients for protein sources is necessary to meet the protein needs in the quail. Hydrolyzed feather of broiler chicken meals is a feed material that has a high protein content, but low potency digestibility. It is expected that the hydrolysis process improves the digestibility in feather meal. The level of digestibility of the ingredients will affect the rate of metabolism of nutrients (proteins) in the body of the quail. The metabolic process of the protein compounds also has the potential to influence the characteristics of quail meat. The purpose of this study was to evaluate the characteristics of quail meat by eating broiler feathers resulting from the hydrolysis process of feed at different levels. This study used 100 heads quail one week old, body weight range 140-180g, (unsex). The study was designed using a completely randomized design (CRD) unidirectional a 4 x 5 pattern. A total of four types of feeding treatment has been applied in this study, namely: (T0 = 0%, T1 = 1%, T2 = 1.5 and T3 = 2%. Each treatment was repeated five times. The number of treatment units was a 4 x 5 = 20 treatment units. Each treatment unit used five head quails as samples. The observation process was carried out for 30 days. On the 30 th, the slaughtering process was carried out and then the meat quality test was continued. The test samples of the quality of the meat were obtained from the chest muscular ( Pectoralis superficialis ). Observations of parameters include: (1) the water holding capacity (WHC), (2) cooking loss (CL) and (3) meat shear force (MSF). The data obtained were analyzed statistically using ANOVA. The results of the research data show significant effect and then Duncan's test. The results showed that the treatment of the feather meal hydrolyzed at different levels significantly (p<0.05) in the WHC, CL, and MSF. The WHC value of breast meat ( Pectoralis superficialis ) in the range of 32.42± 6.24-49.48±11.63%, CL (3.05±2.00-22.30±14.26%) and MSF (0.56±0.26-0.99±0.10 kg/cm 2 ). The use of feeds from the broiler meal at 1.5% (T2 ) level shows the characteristics of quail meat better than other treatments.